(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The ECG plays a key role in the rapid diagnosis of heart diseases such as coronary heart disease, ischemic heart disease, myocardial infarction, arrhythmias, etc. Unfortunately, the adhesion of conventional electrodes to the skin sometimes is difficult if not impossible due to the wet skin caused by higher perspiration. Besides, for the application of long term ECG monitoring, the wet adhesive ECG electrodes are easy to cause infection of the wearers' skin. Moreover, in certain situations it is difficult or simply too time-consuming to undress the patient for an ECG. Therefore, novel ECG monitoring techniques are urgently needed. In this paper, an easy-to-use noncontact ECG (NCECG) monitoring node for wireless body sensor network was designed and tested. The NCECG node introduced in this paper use the doubled shielded active ECG electrodes, compared with many other two electrodes noncontact ECG monitoring node, it also added a right-leg-drive circuit to reduce the common mode noise. The experiment result shows that it could accurately monitor the ECG signals while insulated by one layer of clothes. Furthermore, the NCECG monitoring node we proposed is high compact and easy to use. Besides ECG monitoring function, it also integrates with temperature, respiration and motion state monitoring function, while the size of the circuit board is just 93 00d7 40 mm. And the elastic belt architecture makes the ECG monitoring much more convenient and easy to use.